2016
DOI: 10.1007/s00128-016-1846-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential Toxicities of Nickel Salts to the Nematode Caenorhabditis elegans

Abstract: This study focused on assessing whether nickel (Ni) toxicity to the nematode Caenorhabditis elegans was affected by the molecular structure of the Ni salt used. Nematodes were exposed to seven Ni salts [Ni sulfate hexahydrate (NiSO4·6H2O), Ni chloride hexahydrate (NiCl2·6H2O), Ni acetate tetrahydrate (Ni(OCOCH3)2·4H2O), Ni nitrate hexahydrate (N2NiO6·6H2O), anhydrous Ni iodide (NiI2), Ni sulfamate hydrate (Ni(SO3NH2)2·H2O), and Ni fluoride tetrahydrate (NiF2·4H2O)] in an aquatic medium for 24 h, and lethality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The current result supports our earlier reports where we have shown that Ni induces lethality in developing C. elegans at very low concentrations [16]. Other studies have also corroborated that Ni exposure reduces C. elegans survival from larval stages to adults [28][29][30]. Similarly, other studies have established Ni toxicities in both human and vertebrate animal models, particularly its neurotoxic effects [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The current result supports our earlier reports where we have shown that Ni induces lethality in developing C. elegans at very low concentrations [16]. Other studies have also corroborated that Ni exposure reduces C. elegans survival from larval stages to adults [28][29][30]. Similarly, other studies have established Ni toxicities in both human and vertebrate animal models, particularly its neurotoxic effects [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…For a long time, different toxicity tests with metals and metallic salts have been carried out [46,47], proving to be a predictor of acute lethality in mammals, generating LC50 values parallel to LD50 values for the rat and mouse, since LC50 values were compared to the oral LD50 values published in mammals for the salts of the same metals [48,49].…”
Section: Figure 2 Percentage Of Individual Alive (C Elegans) Versus B...mentioning
confidence: 99%